Role of connexins in human congenital heart disease: the chicken and egg problem - Salameh, Aida; Blanke, Katja; Daehnert, Ingo (Frontiers in Pharmacology, 2013)
Inborn cardiac diseases are among the most frequent congenital anomalies and are the main cause of death in infants within the first year of age in industrialized countries when not adequately treated. They can be divided into simple and complex cardiac malformations. The former ones, for instance atrial and ventricular septal defects, valvular or subvalvular stenosis or insufficiency account for up to 80% of cardiac abnormalities. The latter ones, for example transposition of the great vessels, Tetralogy of Fallot or Shone's anomaly often do not involve only the heart but also the great vessels and although occurring less frequently these severe cardiac malformations will become symptomatically within the first months of age and have a high risk of mortality if the patients remain untreated. In the last decade there is increasing evidence that cardiac gap junction proteins, the connexins (Cx), might have an impact on cardiac anomalies. In the heart mainly three of them (Cx40, Cx43 and Cx45) are differentially expressed with regard to temporal organogenesis and to their spatial distribution in the heart. These proteins, forming gap junction channels, are most important for a normal electrical conduction and coordinated synchronous heart muscle contraction and also for the normal embryonic development of the heart. Animal and also some human studies revealed that at least in some cardiac malformations alterations in certain gap junction proteins are present but until today no particular gap junction mutation could be assigned to a specific cardiac anomaly. As gap junctions transmit growth and differentiation signals from cell to cell it is reasonable to assume that they are somehow involved in misdirected growth present in many inborn heart diseases playing a primary or contributory role. This review addresses potential role of gap junctions in the development of inborn heart anomalies like the conotruncal heart defects.